REVIEW OF THE QUALITY OF SERVICE OF EDUCATIONAL STAFF TO STUDENTS IN MAJOR D-3 HOSPITALITY, UNIVERSITAS PERJUANGAN TASIKMALAYA, TASIKMALAYA, INDONESIA - R. Soni Sumali; Tuti Iriani (International Journal of Social Science, 2025)
Service quality is very important in an academic transaction process, especially for the University of Struggle Tasikmalaya which has a D-3 Hospitality Study Program where students will enter the world of the hospitality industry which has its own service characteristics and is different from one another. In preparing skilled workers who are in accordance with existing hotel industry standards, educators as service providers are the parties who deliver services that are assessed based on service quality elements: attendance, job knowledge, dependability, personality,discipline, adaptability, quality, grooming, organizing, leadership. The overall research results show that the 10 service qualities delivered by the teaching staff are in accordance with the expectations and needs of the student learners, with reference to the applicable hotel industry standards.